Health Literacy – a review of research using the European Health Literacy Questionnaire (HLS-EU-Q16) in 2010-2018 - Niedorys, Barbara; Chrzan-Rodak, Agnieszka; Ślusarska, Barbara (Nursing in the 21st Century, 2020)
HEALTH LITERACY – A REVIEW OF RESEARCH USING THE EUROPEAN HEALTH LITERACY QUESTIONNAIRE (HLS-EU-Q16) IN 2010-2018 Introduction. The concept of health literacy is often used as “health competence”, “health ability. It involves the skills and motivation of people to obtain and understand health information. To improve health understanding and assessment of health literacy, many instruments have been developed to measure health competences in different populations. Among them there is the multidimensional, comprehensive questionnaire HLS-EU-Q16, developed by the Consortium of European Countries. Aim. Review of health literacy studies using the European Health Competence Questionnaire (HLS-EU-Q16) based on literature analysis. Method. Thematic review, unsystematic literature covering the years 2010-2018. The number of 17 source items was analyzed by the authors. Results. The overall level of health literacy was higher in European research than in non-European research. Low levels of health literacy were found in the elderly and chronically ill, immigrants and prisoners, as well as people with low education. The analysis of the research shows that the limited health skills of the respondents are related to the deterioration of the functional state and cognitive skills in the elderly. The decisive determinant of the low level of health literacy among immigrants and prisoners is unemployment and low level of education. Adequate health education plays a key role in improving the social level of health awareness and contributes to the long-term health of the entire population.